Comparison of Performances of Different Types of Clarifiers for the Treatment of Oily Wastewater Produced from Polymer Flooding. (21st May 2015) - Zhang, Jian; Jing, Bo; Tan, Guorong; Zhai, Lei; Fang, Shenwen; Ma, Yongzhang
<x xml:space="preserve">Abstract</x> In this paper, oily wastewater produced from polymer flooding (OWPF) was treated with two different types of clarifiers. One was a cationic polymer (copolymer of acrylamide and acryloyloxyethyl trimethyl ammonium chloride) PAM‐DAC, the other was the non‐ionic polymer (polyoxyalkylated polyethyleneimine) PEI11. The effects of operating conditions on the performances of PAM‐DAC and PEI11 were compared. The performance of PAM‐DAC was not affected by temperature, while temperature had a great influence on that of PEI11. In the same conditions, to obtain the same oil removal performance, PEI11 needed more stirring time, higher dosage, and stronger stirring than PAM‐DAC. The flocs of PAM‐DAC and PEI11 were also different. The PAM‐DAC flocs were viscous and could adhere to the beaker, while the flocs of PEI11 could not. These performance differences were related to their flocculation mechanisms. The results of zeta potential, interfacial tension, and interfacial dilational rheology showed that the flocculation mechanisms of PAM‐DAC were electrostatic charge neutralization and bridging, while the mechanism of PEI11 was demulsification. This comparison is useful for the selection of clarifiers for the treatment of OWPF.